Creative Center of Youth Exellence in the Environmental Sciences and a Tool for Eco-Education - Popovski, Z.T.; Pejovski, E.; Nestorovski, T.; Najdoski, M.; Miskoska-Milevska, E.; Karadelev, M.; Rusevska, K.; Miloseski, J.; Zajkov, O.; Trojacanec, S.; Ristevski, P.; Popovski, T. (Macedonian Ecological Society, 2016)
Creative center Karposh (CCK) is a unique case in Macedonian education system with the mission to provide conditions for interested pupils from the primary schools belonging to Karposh municipality to spend their time out of the classroom in the field of their interest. CCK is composed by ten units that exist in the frame of ten primary schools founded from this local self-government. The units are organized as a synergy of scientists from appropriate fields, young animators, motivated teachers and interested children. The main principle in the functioning is mobility and possibility for circulating of children according their interest nevertheless which unit exists in their own school. All units are closely related to environment and all of them in their programs have a part acknowledged to eco-education. So, in the Climate changes and energy saving unit, children are discovering phenomena of global climate changes and clean alternatives in energy producing. Design and robotics unit is deal- ing with eco-design and usage of natural materials. Environmental protection and recycling unit most of its activity is performing on waste management and re-usage of materials. Audio-visual media is serv- ing as an antenna of all CCK activities including those in the field of ecology. Cultural heritage unit is partially focused on the natural history in Macedonia. Units for zoology and for botany & mycology are developing a culture of biodiversity protection among the children. Threw the Food production and control unit the pupils are involved in production of healthy food and its control. Handicrafts unit is working mostly with natural and recycled material and finally Space science unit is interested in global pollution. All those activities are guaranteeing that via CCK mentioned issues will be brought closer to the younger generations and it will provide environmental friendly coexistence between the nature and civilization in this part of the Planet.
Keywords: extracurricular, gifted children, primary school